SDN-enabled deployment and path planning of aerial base stations - Bozkaya, Elif; Canberk, Berk (Elsevier BV, 2020)
Abstract Aerial Base Stations (ABSs) play a central role in mission critical environments due to the fast deployment, flexible reconfiguration, low cost. In this manner, through the controllable ABSs that are directed to the disaster region, users can continuously remain connected with ABSs. However, ABS deployment and path planning face several key challenges to provide on-demand communication and enable “Quality of Experience (QoE)-guaranteed”service to the users. For example, energy consumption, maximizing the number of covered users and scheduling the ABS’s operations are important issues that need to be considered. Thus, this paper jointly presents a Software Defined Networking (SDN) enabled solution to efficiently deploy ABSs which maximizes the covered users and communication quality, and provides a path planning strategy which decreases the energy consumption. Our simulation is managed with SITL (Software In The Loop) simulator, which allows to create and test drones without a real vehicle using C++ compiler and we confirm the improvement in terms of connectivity and energy consumption when compared to a recent state-of-the-art approach.